Redescription of immatures and bionomy of the Palaearctic species Dicladispa testacea (Linnaeus, 1767) (Coleoptera: Chrysomelidae: Cassidinae: Hispini), a leaf-mining hispine beetle - Świętojańska, Jolanta; Borowiec, Lech; Stach, Małgorzata (Zootaxa, 2014)
Dicladispa testacea (Linnaeus, 1767) is a member of the tribe Hispini Gyllenhal, 1813 associated with plants of the family Cistaceae Juss. and is widely distributed in the Mediterranean Basin. Immature stages are described in detail, including line drawings, chaetotaxy, sculpture of integument, and SEM photos of morphological details. This is the first detailed description of immatures in the tribe Hispini, and this can be regarded as a model description for studies of other species in the tribe. Diagnostic characters for this species in comparison with other described larvae and pupae of the genus Dicladispa and the sympatric Hispa atra Linnaeus, 1767 are discussed. Some remarks on the biology of Dicladispa testacea, such as host plants, feeding patterns of adults, structure of larval and pupal mines, are also given.